Minimal Climate Impacts From Short‐Lived Climate Forcers Following Emission Reductions Related to the COVID‐19 Pandemic. Issue 20 (22nd October 2020) - Weber, James; Shin, Youngsub M.; Staunton Sykes, John; Archer‐Nicholls, Scott; Abraham, N. Luke; Archibald, Alex T.
Abstract: We present an assessment of the impacts on atmospheric composition and radiative forcing of short‐lived pollutants following a worldwide decrease in anthropogenic activity and emissions comparable to what has occurred in response to the COVID‐19 pandemic, using the global composition‐climate model United Kingdom Chemistry and Aerosols Model (UKCA). Emission changes reduce tropospheric hydroxyl radical and ozone burdens, increasing methane lifetime. Reduced SO2 emissions and oxidizing capacity lead to a decrease in sulfate aerosol and increase in aerosol size, with accompanying reductions to cloud droplet concentration. However, large reductions in black carbon emissions increase aerosol albedo. Overall, the changes in ozone and aerosol direct effects (neglecting aerosol‐cloud interactions which were statistically insignificant but whose response warrants future investigation) yield a radiative forcing of −33 to −78 mWm −2 . Upon cessation of emission reductions, the short‐lived climate forcers rapidly return to pre‐COVID levels; meaning, these changes are unlikely to have lasting impacts on climate assuming emissions return to pre‐intervention levels. Plain Language Summary: As a result of the global COVID‐19 pandemic, unprecedented lockdown measures have been imposed worldwide to reduce the spread of the disease, causing huge reductions in economic activity and corresponding reductions in transport, industrial, and aircraft emissions. As well as lowering emissions of greenhouse gases, such as carbon dioxide, this has resulted in a dramatic reduction in the emissions of pollutants that also affect climate. In this study, we have used state‐of‐the‐art computer simulations to quantify how changes in these components are likely to impact the chemical make‐up of the atmosphere and the likely short‐term impacts on climate. Despite large decreases in nitrogen dioxide and atmospheric particles, we find these changes result in a very small impact on the energy balance of the atmosphere but one that would act to cool the planet, without considering the knock‐on impacts on clouds (which we cannot be confident about). However, these effects are all likely to be short‐lived if emissions return to pre‐lockdown levels. Key Points: Emission reductions are likely to have led to a global reduction in short‐lived climate forcers and tropospheric oxidizing capacity Reductions in O3 and aerosol from both lower emissions and decreased sulfate oxidation resulted in a net negative radiative forcing The radiative impacts are small and short‐lived. Longer term climate impacts must come through future sustained emission reductions